Elevating the research and publication culture of the University of the Immaculate Conception Graduate School: A practical action research - SYLVIA J. PIDOR; RENAN P. LIMJUCO; MARY JANE G. BARLUADO (Journal of Advanced Research in Social Sciences and Humanities, 2017)
Aim: In this action research, a strategy is created to meet the demand for increasing the participation of Graduate School (GS) faculty and students at the University of the Immaculate Conception (UIC) in the intensification of UIC’s research and publication culture to bring it up to the same level as its international recognition.Methodology: Purposively selecting 30 participants to represent the various stakeholders of the UIC GS, we used a qualitative descriptive research design called Practical Action Research (PAR) to facilitate brainstorming and exploratory sessions aimed at answering our research objectives, which included the following: a) increasing graduate faculty and student research productivity; b) formalizing mentor-mentee publication authorship; and c) incorporating innovative research pedagogies.Findings: Our research uncovered systemic problems with far-reaching implications that share common causes and potential remedies. Lack of well-articulated policies, research experts, research class directions, and members’ confidence are all issues that regularly arise.Implications/Novelty: To improve the research and publication climate at UIC GS, we came up with a few suggestions as a starting point for a long-term strategy.